2017
DOI: 10.1186/s12889-017-4462-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to evaluate the impact of a geo-specific poster compared to a general poster for effecting change in perceived threat and intention to avoid drowning ‘hotspots’ among children of migrant workers: evidence from Ningbo, China

Abstract: BackgroundDrowning among children of migrant workers is a major, though neglected public health issue in China.MethodsA randomised controlled trial was used to examine the potential impact of viewing a preventive health poster with/without geo-located drowning events on perceptions of drowning risk among Chinese migrant children. A total of 752 children from three schools in Jiangbei district were selected by multi-stage sampling and randomly assigned to the intervention (n = 380) or control (n = 372). Multile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…This group of immigrants tend to work in the industrial estate in Irbid. Where in other studies held by Gallinger et al ( 22 ), Pidgeon et al ( 23 , 24 ), Bona et al ( 25 ), and Zhu et al ( 26 ) demonstrated that immigrants had a high risk of drowning among original citizens.…”
Section: Discussionmentioning
confidence: 87%
“…This group of immigrants tend to work in the industrial estate in Irbid. Where in other studies held by Gallinger et al ( 22 ), Pidgeon et al ( 23 , 24 ), Bona et al ( 25 ), and Zhu et al ( 26 ) demonstrated that immigrants had a high risk of drowning among original citizens.…”
Section: Discussionmentioning
confidence: 87%
“…E-health is a health service conducted through the Internet and related technology, while m-health is a health service utilized through a mobile application (Dang, Golden, Cheung, & Roos, 2010 ;Power, 2018). However, traditional health promotion media, such as posters and leaflets, are still frequently used (Nitschke, Krackowizer, Hansen, Bi, & Tucker, 2017;Zhu et al, 2017). Is the use of traditional media still effective in the current era of digitalization?…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dilakukan untuk pengingat agar para warga serta tamu yang ada di masjid Al-Hidayah tersebut agar selalu dapat menerapkan isolasi mandiri yang benar sesuai dengan peraturan Kemenkes. Spanduk efektif untuk menimbulkan kesadaran seseorang sehingga berpengaruh pada perilakunya (Zhu, et al, 2017).…”
Section: Daftar Pustakaunclassified